Penerapan E-Faktur Dan Web E-Faktur Pada PT. ZAD Konsultama Indonesia Kota Bandung - widiawati, santi; Eka Putri Pratama (LPPM POLITEKNIK LP3I BANDUNG, 2025)
The research method that explains or describes the research according to the events as they are, expressed through documentary materials, observations, and interviews. The data used by the autors in implementing e-Invoice and Web e-Invoice is the application of e-Invoice and Web e-Invoice in PT ZAD Konsultama Indonesia. After discussing the problems, the authors concluded that the application of e-Invoice and Web e-Invoice has been well implemented.